Code division multiple access based multi-channel medium access control protocols and topology control for mobile ad hoc networks - Zhang, Lili (2008)
This thesis presents two novel code division multiple access based multi-channel MAC protocols and proposes the multi-code multi-packet transmission scheme for mobile ad hoc networks, in order to improve the network performance. It also addresses the topology control with respect to k-connectivity under a realistic channel model.